2016
DOI: 10.1037/bul0000041
|View full text |Cite
|
Sign up to set email alerts
|

Friendship in school-age boys with autism spectrum disorders: A meta-analytic summary and developmental, process-based model.

Abstract: Friendship-making is considered a well-established domain of deficit for children with autism spectrum disorders (ASD; American Psychiatric Association, 2013), with this population sometimes described as incapable of making friends. However, the majority of children with ASD indicate a desire for friends, and many report having friends. To what degree, then, do youth with ASD succeed in achieving friendships with peers? If and when they do succeed, by what means do these friendships emerge relative to models o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
78
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 165 publications
7
78
1
3
Order By: Relevance
“…Youth with ASD are at increased risk for social isolation and peer victimization (Hobson, 2014; Mendelson, Gates, & Lerner, 2016). Moreover, social impairments in youth with ASD do not tend to improve merely with development, but rather may become more pronounced during adolescence when the social demands exceed the social skills (Picci & Scherf, 2015), underscoring the need for appropriate interventions to promote social competence in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Youth with ASD are at increased risk for social isolation and peer victimization (Hobson, 2014; Mendelson, Gates, & Lerner, 2016). Moreover, social impairments in youth with ASD do not tend to improve merely with development, but rather may become more pronounced during adolescence when the social demands exceed the social skills (Picci & Scherf, 2015), underscoring the need for appropriate interventions to promote social competence in this population.…”
Section: Introductionmentioning
confidence: 99%
“…High-functioning autism is one of several neuro-psychiatric functional impairments. People who are diagnosed with such are described as having limitations in the areas of social cognition [21][22][23][24][25][26][27][28][29][30] and empathy [31][32][33][34][35]. Research has also identified a lack of enterprise and an inability to take the initiative amongst people who have been diagnosed with high-functioning autism [36,37], as well as a limited ability to make plans and to be flexible [24].…”
Section: High-functioning Autismmentioning
confidence: 99%
“…These essential features and their associated symptoms and conditions significantly impact social functions across the lifespan [Lai et al, ]. During childhood and adolescence, these ASD core symptoms may lead to dysfunction and maladaptive outcomes in the school setting, such as academic underachievement, fewer reciprocal friendships, interpersonal difficulties and poor adaptation at school [Mendelson, Gates, & Lerner, ; Rotheram‐Fuller, Kasari, Chamberlain, & Locke, ]. They are expected to have discrepant academic achievement based on their overall intellectual ability [Jones et al, ; Nation, Clarke, Wright, & Williams, ].…”
Section: Introductionmentioning
confidence: 99%